Renegotiating the food aid convention - Hoddinott, John F.; Cohen, Marc J. (International Food Policy Research Institute, 2007)
The current global agreement governing food aid—the Food Aid Convention (FAC)—will expire in 2007. It has come under heavy criticism as has the diffuse set of broader food aid governance institutions that has emerged in the last 50 years. These institutions are characterized by overlapping mandates, differing degrees of authority and legitimacy, varied levels of transparency in decisionmaking, and problematic representation of the major stakeholders. A number of issues are likely to arise during the course of negotiations over a new FAC. These include its objectives; the nature of commitments—whether to express them in tonnage, value, or nutritional terms; the level of commitments and their distribution among donor countries; monitoring and enforcement of commitments; representation on the FAC governing body among food aid donor- and recipient-country governments and civil society organizations; and the institutional “home” of the FAC. More specifically, there is debate over such questions as whether the new FAC should have an “instrument focus”—food aid—or a “problem focus” such as “food security” or “hunger.” If the focus is on addressing hunger, should food aid under the FAC be restricted to emergencies only or should it pertain to broader food security issues? Should the FAC be a low-key forum for exchange of information or should it have some meaningful ways of monitoring commitments and encouraging compliance by both donors and recipients? Debates such as these will reflect views on the purposes of food aid itself. Conversely, debates regarding these broader questions carry consequences for the formation of views on the issues involved in the FAC negotiations. This paper’s purpose is solely to outline issues and options; hence it does not advocate for particular positions.